Characterization and Effectiveness of Moringa Leaves (Moringa oleifera Lamk.) And Azotobacter chroococcum Bio-Organic Fertilizer on the Growth of Green Spinach - Elli Afrida; Benny Hidayat (Talenta Publisher, 2026)
The decline in spinach production is a challenge in sustainably increasing its productivity. One potential solution is the use of bio-organic fertilizer (BOF) derived from leaves of Moringa (Moringa oleifera Lamk.) and Azotobacter chroococcum because it contains essential nutrients for plant growth. This study aims to characterize moringa leaf BOF and its effectiveness in increasing green spinach growth (Amaranthus tricolor L.). The research was conducted experimentally using five treatments: P1 (10% Moringa leaves), P2 (15% Moringa leaves), P3 (20% Moringa leaves), K⁻ (0% Moringa leaves), and K⁺ (Commercial Fertilizer). Observed parameters included fertilizer pH, temperature, color, plant height, and number of leaves. Fertilizer observation data were analyzed descriptively based on SNI standards and credible journals, while plant growth data were analyzed using ANOVA and ANCOVA at a 5% significance level. The BOF produced had a pH of 6–7, a temperature of 26–27 °C, and a dark brown color. The best performance was obtained with treatment P3, producing an average plant height of 26.6 cm and 14 leaves. These findings indicate that Moringa leaf-based BOF has potential as an effective and environmentally friendly organic fertilizer to improve green spinach growth.